HUMANISME SEBAGAI FILSAFAT HUKUM ISLAM - Nur Kholis (Faculty of Sharia and Law UNISNU Jepara, 2014)
There are two (2) issues of humanism regarding to the philosophy of Islamic law. First, humanism either as the movement of the humanities or the schools of philosophy, in the West (Christian) and the East (Islam)-grows and evolves in the dialectic of human life that is characterized by tendency to deny the others. Fundamental rights of human in the socio-cultural history is proved repeatedly crushed by the interests of abstract theology, exclusive ideology, massive feudalism, and lack of empathy for the weak. On the basis of this ridiculous